Of filming thrillers and domestic abuse: The courage we need - Salmiah, Abdul Hamid (Buro 24/7 Malaysia Website, 2016)
Faculty of Applied and Creative Arts's Alumni from Cinematography Programme recently won Sundance Channel Short Film Contest grand prize for a thriller movie entitled "The Return".